Predictors of worsening TR severity after right ventricular lead placement: any added value by post-procedural fluoroscopy versus three –dimensional echocardiography? - Hoorak Poorzand; Mohammad Tayyebi; Sara Hosseini; Alireza Heidari Bakavoli; Faeze Keihanian; Lida Jarahi; Ali Hamadanchi (Cardiovascular Ultrasound, 2021)
Abstract Background The effect of right ventricular (RV) leads on tricuspid valve has been already raised concerns, especially in terms of prognostic implication. For such assessment, three-dimensional transthoracic echocardiography (3D-TTE) has been used previously but there was no data on the use of post-procedural fluoroscopy in the literature. Methods We prospectively enrolled 59 patients who underwent clinically indicated placement of pacemaker or implantable cardioverter defibrillator (ICD). Vena contracta (VC) and tricuspid regurgitation (TR) severity were measured using two-dimensional transthoracic echocardiography (2D-TTE) at baseline. Follow up 3D-TTE was performed 6 months after device implantation to assess TR severity and RV lead location. Results Lead placement position in TV was defined in 51 cases.TR VC was increased after the lead placement, compared to the baseline study (VC: 3.86 ± 2.32 vs 3.18 ± 2.39; p = 0.005), with one grade worsening in TR in 25.4% of cases. The mean changes in VC levels were 1.14 ± 0.67 mm. Among all investigated parameters, VC changes were predicted based on lead placement position only in 3D-TTE (p < 0.001) while the other variables including fluoroscopy parameters were not informative. Conclusion The RV Lead location examined by 3D-TTE seems to be a valuable parameter to predict the changes in the severity of the tricuspid regurgitation. Fluoroscopy findings did not improve the predictive performance, at least in short term follow up.